The Effect of Government Expenditure on Districts and City in Bali Province, Indonesia - Feny Gusti Wijayanti; Wardatul Fara; Huswatun Hasanah (Proceedings of Bengkulu International Conference on Economics, Management, Business, and Accounting, 2023)
This study aims to determine the effect of tourism, health, infrastructure and the economic expenditures, as well as the Covid-19 pandemic on unemployment and poverty in the Regency/City of Bali Province, Indonesia. The research data used is panel data, consisting of nine regencies and cities in Bali Province 2014-2021. The analysis method used is panel data regression. The results showed that infrastructure expenditure has a significant negative effect on the unemployment rate. Economic expenditure has a significant positive effect on unemployment. During the Covid-19 pandemic, the unemployment rate increased significantly in Bali Province. Meanwhile, infrastructure expenditure and health expenditure have a significant negative effect, and economic expenditure has a significant positive effect on the poverty rate. However, the Covid-19 pandemic did not cause the poverty rate to increase significantly in Bali Province.